2018
DOI: 10.1007/s10750-017-3499-2
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits and demographic parameters in the Keratella cochlearis (Rotifera, Monogononta) species complex

Abstract: A recent study based on DNA taxonomy indicated that the widespread rotifer Keratella cochlearis comprises several evolutionarily significant units (ESUs). Identification of ESUs based on DNA taxonomy alone is problematic and usually requires morphological, demographic, and/or ecological evidence. We isolated three haplotypes belonging to two ESUs of K. cochlearis and conducted life table experiments to investigate if this genetic diversity is reflected in demography. We found significant differences between ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Amphoteric females occur in some rotifers and provide an additional mechanism to assure continued female parthenogenesis during sexual periods. These females produce haploid eggs developing into males or resting eggs, and also amictic eggs developing into females (reviews in Cieplinski, Obertegger, & Weisse, 2018;Gilbert, 2007;Rico-Martínez & Walsh, 2013). They usually are rare; for example, only 0.35% of females in a cultured population of Keratella cochlearis from Lake Tovel (northern Italy) were amphoteric (Cieplinski et al, 2018).…”
Section: Ecological Significance Of Some Female Parthenogenesis Durmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphoteric females occur in some rotifers and provide an additional mechanism to assure continued female parthenogenesis during sexual periods. These females produce haploid eggs developing into males or resting eggs, and also amictic eggs developing into females (reviews in Cieplinski, Obertegger, & Weisse, 2018;Gilbert, 2007;Rico-Martínez & Walsh, 2013). They usually are rare; for example, only 0.35% of females in a cultured population of Keratella cochlearis from Lake Tovel (northern Italy) were amphoteric (Cieplinski et al, 2018).…”
Section: Ecological Significance Of Some Female Parthenogenesis Durmentioning
confidence: 99%
“…These females produce haploid eggs developing into males or resting eggs, and also amictic eggs developing into females (reviews in Cieplinski, Obertegger, & Weisse, 2018;Gilbert, 2007;Rico-Martínez & Walsh, 2013). They usually are rare; for example, only 0.35% of females in a cultured population of Keratella cochlearis from Lake Tovel (northern Italy) were amphoteric (Cieplinski et al, 2018). However, they can be common in S. socialis (Bogoslavsky, 1958;Champ & Pourriot, 1977;Rico-Martínez & Walsh, 2013) and Conochiloides (now Conochilus) dossuarius (Bogoslavsky, 1960).…”
Section: Ecological Significance Of Some Female Parthenogenesis Durmentioning
confidence: 99%
“…This is the first study to contribute evidence of genetic differences in temperature tolerance between two neighboring populations of K. cochlearis with location-specific temperature variations. To date, only one study has demonstrated that genetically different haplotypes of K. cochlearis also differ in their growth rate and in other demographic parameters (Cieplinski et al, 2018). The authors had investigated differences between two ESUs of K. cochlearis at the same temperature (14.5°C).…”
Section: Different Responses Of Fitness To Temperaturementioning
confidence: 99%
“…Moreover, mitonuclear discordance in the delimitation of ESUs was recently reported for K. cochlearis species complex (Obertegger et al, 2018). Therefore, the identification of ESUs based on DNA sequences alone is problematic, and usually requires morphological, demographic and/or ecological evidence (Cieplinski et al, 2018;Obertegger et al, 2018). However, despite ample genetic variation among genotypes and populations, there has been no published research on the local adaptability of this species complex.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior spine presents high morphological variations ranging from its total absence to a large and rigid spine (Segers & De Smet, 2008). The factors related to this variation are temperature, trophic conditions, mutation accumulation, and predator presence (Stemberger & Gilbert, 1987;Galkovskaja & Mityanina, 1989;Bielanska-Grajner, 1995;Cieplinski et al, 2018). However, recent studies have demonstrated that some pollutants can cause a variety of morphological and reproductive effects on different groups of zooplankton (Elmoor-Loureiro, 2004;Zurek, 2006;Alvarado-Flores et al, 2015;Pérez-Yáñez et al, 2019).…”
mentioning
confidence: 99%